Study of Serum Leptin Level in Patients Diabetes Mellitus Type 2: in Relation with Insulin Level - Sadeq, Mateen; Sarı, Aysel (Sivas Cumhuriyet Üniversitesi, 2022)
Leptin is a food intake hormone. Informed leptin diet provides adequate nutrition. Leptin plays an important role in T2DM. Having high leptin and being in love is not a reason for preference. Evaluation of serum and ptin levels in T2DM patients and healthy patients, and the relationship between serum fasting insulin and leptin in T2DM. In the endocrine and market cross-sectional education, a total of 92 serums were studied, including 70 patients with T2DM and 22 patients who were not healthy. Serum leptin was measured by ELISA, serum insulin autoanalyzer Cobas E411. Hemoglobin was studied with HPLC D10. Posting regarding serum leptin and insulin, fasting and BMI. In this study, a significant relationship was observed between leptin and insulin and T2DM, and a significant positive relationship between leptin and insulin (p
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi